Finance and Development, June 1967. (Finance and Development; Finance and Development, 1967)
The paper discusses development of smallholder tea cultivation and a new breed of planters in Kenya. As the work of land consolidation and registration progressed in Kenya, tea planting in areas that were ecologically suitable became increasingly popular. The paper highlights that with the help of some USD 3 million from the International Development Association, about 900 miles of tea collection and factory access roads are being constructed in the various tea-growing areas of Kenya, and some 15 small road maintenance units are being established and equipped.